Leveraging Social Determinants of Health to Enhance Recruitment of Underrepresented Populations in Clinical Trials - Sara King; Sophia Trabanino; Zahra Azizi; Fatima Rodriguez (Methodist DeBakey Cardiovascular Journal)
Historically marginalized communities are disproportionately affected by cardiometabolic diseases yet are underrepresented in clinical trials that investigate needed interventions. This review investigates the barriers to equitable inclusion in clinical trials, identifying opportunities for improvement at the institutional, trial, community, and individual level. It proposes a social determinants-based approach that serves as a toolkit to target these barriers using structural, economic, community, healthcare access, and technology solutions, supporting constructive improvement in the clinical trial recruitment process.